Cachexia but not obesity worsens the postoperative outcome after pancreatoduodenectomy in pancreatic cancer - Pausch, Thomas; Hartwig, Werner; Hinz, Ulf; Swolana, Thomas; Schwarz-Bundy, Bogáta D.; Hackert, Thilo; Grenacher, Lars; Büchler, Markus W.; Werner, Jens (Surgery, 2012)
Background. Prognosis after pancreatoduodenectomy for pancreatic cancer is determined by tumor characteristics, completeness of resection, and patient's comorbidity. Our aim was to assess the effects of body mass and fat distribution on the postoperative course after pancreatoduodenectomy. Methods Of 2,968 pancreatic resections, 408 patients with primary pancreatic adenocarcinoma who underwent pancreatoduodenectomy and of whom cross sectional images were available were identified and followed-up in a prospective database. Preoperative computed tomographic or magnetic resonance imaging scans were analyzed for abdominal wall fat, hip girdle fat, visceral fat, and abdominal depth. Peri- and postoperative parameters, including preoperative unintentional weight loss, cachexia-associated serum parameters, nonoperative and operative complications, and mortality and long-term survival were evaluated and correlated with body mass index and fat distribution. Results Patients with low body mass index had a greater 90-day mortality (P = .048) and a trend toward greater complication rates and in-hospital mortality, despite a greater comorbidity in obese patients with a higher body mass index. Accordingly, patients with large amounts of abdominal wall fat had fewer intra-abdominal abscesses (P = .047), lower in-hospital (P = .019) and 90-day mortality rates (P = .007), and better long-term survival (P = .016). Conclusion In pancreatic cancer, underweight but not obese patients have a poor outcome after pancreatoduodenectomy. This observation emphasizes the need for pre- and perioperative therapeutic improvements in the setting of pancreatic cancer-associated cachexia.